Numerical, Mechanical, and Metallurgical Investigation of an Innovative Near Net Shape Titanium Selective Laser Melting Engine Component and Comparison with the Conventional Forged One. Issue 7 (10th April 2021) - Cecchel, Silvia; Ferrario, Davide; Mega, Francesco; Cornacchia, Giovanna
Abstract : Selective laser melting (SLM) can be used to manufacture near net shape (NNS); the main benefits are a remarkable weight reduction, a lower environmental impact, the opportunity to integrate some functions, and an improvement of the performances. The current article covers the development of a Ti6Al4V NNS engine component produced by SLM. Finite element analyses of the main relevant operating conditions are performed to reach a topological optimization of the part. The main target is weight reduction keeping the same safety performances. The weight reduction achieved is 45% and 15% with respect to steel and titanium forging by replacing the original "H" section with an SLM multibranch structure. Other benefits are the manufacturing of the connecting rod (conrod) into two separate parts, avoiding the difficult machining to separate the cap from the main body and the integration of conformed cooling channels into the conrod. Then, the SLM components are produced and mechanical and metallurgical properties are investigated and compared with the titanium hot forging ones. Both the macrostructures present equiassic and isotropic behavior due to the heat treatment transformation. No defects are observed for both the technologies. The mechanical properties are verified to be aligned with the design targets. Abstract : The main purpose of the article is to apply selective laser melting (SLM) to reduce the weight of a high‐performance Ti6Al4V engine component. A topological optimization leads to 15% weight reduction. The SLM components are produced and mechanical and metallurgical properties are investigated and compared with the titanium hot forging ones. The properties are verified to be aligned with the targets.